Perbedaan Representasi Sosial Tentang Siswa Junior antara Siswa Kelas XII SMAN A Dan SMAN B - Asri Christine Lubis; Ferdinand Prawiro (Universitas Katolik Indonesia Atma Jaya, 2016)
Seniority is a social phenomenon that is naturally found in the school environment. At SMAN A, seniority has been abused by senior students. Meanwhile, at SMAN B, seniority has been applied positively. This difference indicates that there were unique meanings given to the junior students by the seniors in the two schools. This study aims to understand these differences by using social representations theory with the structural approach. The study was conducted in two stages. Free association method was used in the first stage to discover the attributes of social representation of junior students. Researchers asked 206 participants at SMAN A and 198 participants at SMAN B to write down the things that came to mind when they read the word